Pengabdian Masyarakat sebagai Narasumber dalam Webinar Ngobrol Bareng Legislator Untuk Peningkatan Kesadaran Perlindungan Data Pribadi - Surbakti, Feliks Prasepta Sejahtera (Jurnal Pengabdian Masyarakat Charitas, 2024)
With the growing digital transformation, ensuring cybersecurity has become crucial, especially concerning personal data protection. This event, titled "Jangan Asal Sebar Data Pribadi," aimed to raise awareness about the legal framework and best practices for safeguarding personal data in Indonesia. The discussion, held on March 1, 2023, covered key regulations such as the Personal Data Protection Law (UU No. 27 of 2022), which sets strict penalties for unauthorized dissemination of personal information. The session also introduced the "8 Digital Safety Indicators," which include managing privacy on social media, reporting misuse, disabling geographic tracking, and adopting strong password practices. These steps, along with utilizing antivirus software and twofactor authentication, are essential in protecting individuals from phishing, malware, and data theft. The event concluded with actionable solutions to mitigate common cyber threats like fake APK files sent through messaging apps. This seminar underscored the importance of digital literacy and vigilance in maintaining cybersecurity and emphasized the need for individuals and organizations to implement robust data protection strategies. The discussion highlighted the growing importance of safeguarding personal data to prevent security breaches and protect privacy.